(untitled) (Journal of Technology and Operations Management, 2019)
This study aims to develop the need to create PISA type problems using the Yogyakarta context that is designed to obtain student literacy skills. This research is a type of development research by adapting the Tessmer development model. This research was carried out in two stages, namely the preliminary stage, starting from the preparation and design, then the evaluation stage, which included self-evaluation, prototype making, small groups, and field tests. This research is limited to making prototypes. The subjects of this study were grade IX students of SMP Negeri 3 Depok, Indonesia. Data collection instruments consist of a collection of observations, interview guidelines, documentation sheets, and questionnaires. Data were analyzed with qualitative and quantitative techniques. The results showed that the design of the type of PISA that had been developed was declared valid; it could be used in the development of small groups and field tests. Thus, PISA design in the Yogyakarta context can be used by students, both with low, medium, and high abilities according to the needs of students in the industrial revolution era 4.0.